What is (and what is not) Cytisus cantabricus? - Fernández Prieto, José Antonio; Fernández, Herminio S. Nava; Fernández Casado, María De Los Ángeles; Gallastegui, Mercedes Herrera; Sánchez, Álvaro Bueno; Sanna, Mauro; Cires, Eduardo (Phytotaxa, 2017)
Major changes in the diagnosis, taxonomy and chorology of Cantabrian brooms with glabrous calyces and pubescent legumes, classified as sect. Spartopsis of the genus Cytisus (Fabaceae), have been recently implemented. Two species of this section occur in the Cantabrian region: Cytisus cantabricus and C. grandiflorus. A detailed study of the plants usually identified as C. cantabricus demonstrates that, if the shape of the branches and the types of leaves are considered, the current species C. cantabricus includes two discrete taxa and we describe C. dieckii as this second species. Both C. cantabricus and C. dieckii are endemic to the Cantabrian region, have been characterized, and both lectotypes have been chosen. Evidence of the presence of Cytisus grandiflorus in these territories has not been found.